Automatic stabilizers: The intersection of labour market and fiscal policies - Torben M. Andersen (IZA Journal of European Labor Studies, 2016)
The Great Recession has revived aggregate demand management policies. In particular, automatic stabilizers are praised since they are rule based and thus operate swiftly and symmetrically across the cycle. However, automatic stabilizers are not a result of macro design but the structure of the social safety net and the taxation system. The participation tax is a key determinant of the strength of the automatic stabilizers. Paradoxically, the disincentive effects of high participation taxes are often discussed at the same time as automatic stabilizers are praised. The paper considers the sources of automatic stabilizers and whether they (un)intentionally have been weakened via structural reforms to strengthen work incentives. It is considered whether it is possible to maintain strong automatic stabilizers without jeopardizing incentives via the design of the social safety net (workfare) or business cycle-dependent unemployment insurance. The criticism that automatic stabilizers may prolong downturns is also considered. Finally, it is discussed to what extent aggregate demand management policy can stabilize labour markets and, in particular, whether it is well targeted towards marginalized groups. Also, the potential sources of marginalization in the labour market are discussed.
Keywords: E62; H24; H61; J60; 330